Essential oils profile and biological activities of litsea spp. And cinnamomum spp. (lauraceae) - Wan Nur Aishah, Bt Wan Abdullah (Universiti Malaysia Sarawak (UNIMAS), 2013)
The essential oils from various parts of Lilsea nidularis, Lilsea resinosa, Cinnamomum javanicum and Cinnamomum microphyllum (Lauraceae) was extracted using hydrodistillation method. The essential oils obtained were analyzed using Gas Chromatography Mass Spectrometry (GC-MS). The percentage of essential oil extracted from two Lilsea spp ranged from 0.5% to 1.5% (v/w). The percentage of essential oils from two Cinnamomum spp. ranged from 1.20% to 8.12%. The highest yeild of oils was obtained from the roots of C. javanicum(8.12%) and lowest oils obtained from the barks of C. microphyllum (1.20%). The root oil and the leaves oil of L. resinosa was rich in (Z, E) - a-famesene (12.40%) and cadina-3, 9-diene (27.11 %). Elixene was the highest composition compound in the bark oil of L. nidularis with 9.17% compared to the leaves oil which was rich in selina-6-en-4-o1 (20.62%). The bark, leaves and root oil of of C. javanicum was rich in I-Isopropyl-4, 8-dimethylspiro [4.5] dec-8-en-7-one (18.97%), 3,5-Diisopropylphenol (12.79%) and eugenol methyl ether (23 .67%) respectively. The leaves oil of C. microphyllum was rich in longipinocarveol (18.48%) while the bark oil of C. microphyllum was rich in 6-Isopropenyl-4, 8a-dimethyldecahydro-I-naphthalenol (22.29%). Toxicity test against brine shrimp Artemia salina showed that some of the essential oil from Lilsea spp. and Cinnamomllm spp. were toxic. The leaves oil ofL. nidularis and bark oil of C. javanicllm showed the highest toxicity with LCso less than 101lg/mL which showed 100% mortality at concentration of 101lg/mL.